2004
DOI: 10.1016/j.virusres.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Harmonising the virological surveillance of influenza in Europe: results of an 18-country survey

Abstract: The European influenza surveillance scheme (EISS) is based on a surveillance model that combines clinical and virological data in the general population. Eighteen countries in Europe report weekly influenza activity to EISS (http://www.eiss.org). A questionnaire on the virological data collection was sent electronically to the EISS members. Questions on the specimen collection, representativity, laboratory diagnosis of influenza, reporting of variants, testing for other respiratory infections, serological test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Estimated rates based on ILI and ARI consultations showed great variability across countries, most likely due to different health systems, healthcare‐seeking behavior, and surveillance schemes, including case definitions and virological surveillance . The WHO Regional Office for Europe and the ECDC receive weekly information on ILI and/or ARI from surveillance systems using either population or consultation denominators as well as qualitative indicators such as intensity, trend, and geographical spread, by country.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated rates based on ILI and ARI consultations showed great variability across countries, most likely due to different health systems, healthcare‐seeking behavior, and surveillance schemes, including case definitions and virological surveillance . The WHO Regional Office for Europe and the ECDC receive weekly information on ILI and/or ARI from surveillance systems using either population or consultation denominators as well as qualitative indicators such as intensity, trend, and geographical spread, by country.…”
Section: Discussionmentioning
confidence: 99%
“…A study in UK found only about 30% of specimens from patients presenting with ILI symptoms in a general practitioner's surveillance network were positive for influenza [8] . Laboratory surveillance, which is believed to provide more accurate information about influenza virus activity than clinical surveillance, has been implemented in parallel with clinical surveillance in many regions [9] , [10] . Unfortunately, due to constraints of time and budget, laboratory surveillance tends to be more restricted in scale with relatively smaller numbers of patients being tested with the primary aim of detecting genetic and antigenic changes of circulating strains in order to update influenza vaccines rather than for early warning of influenza epidemics [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Many of the European primary care-based surveillance networks for monitoring influenza also report on the incidence of RSV infection. However, although these networks investigate for both viruses, they do so in patients presenting with what are generally described as ILI [22]. Whilst not all networks collect data on the basis of strict diagnostic criteria, there is a general consensus of investigating patients with illnesses which include acute onset of respiratory symptoms such as cough accompanied by fever.…”
Section: Introductionmentioning
confidence: 99%